Perspektif Tri Kaya Parisudha Dan Karma Phala Pada Akuntabilitas Auditor Dengan Moderasi Beragama Sebagai Variabel Intervening - Ni Putu Ari Aryawati; Ni Nyoman Kerti Yasa; Ida Bagus Raka Suardana (Jayapangus Press, 2022)
This study analyzes whether tri kaya parisudha, karma phala and religious moderation directly effect auditor accountability which tri kaya parisudha and karma phala indirectly effect auditor accountability with religious moderation as a mediating variable. This study are conducted in Mataram City with respondents being auditors in various sectors. This study used a questionnaire instrument as a data collection method. Analysis of the data in this research used Partial Least Square (PLS) 23.0 analysis. The results of direct analysis show that tri kaya parisudha affect positive significant to religious moderation and did not affect significantly to auditor accountability, karma phala affect positive significant to religious moderation and did not affect significantly to auditor accountability, and religious moderation directly affect positive significant ton auditor accountability. Tri kaya parisudha and karma phala influence full mediation on auditor accountability with religious moderation as an intervening variable. The results of this study contribute to support the role theory and provide an understanding of the influence of auditors spiritual capital in the perspective of tri kaya parisudha and karma phala. Auditors are expected to be able to use good thoughts to plan audits, take appropriate actions according to the code of ethics in conducting and deliver the correct audit results without being separated from the independence and professionalism of the auditors.